Securitization, Desecuritization, and Resecuritization of Labor Issues in Saudi Arabia - Muhammad Riza Hanafi; Mely Noviryani (Politicos: Jurnal Politik Dan Pemerintahan, 2024)
The presence of Indonesian Workers (TKI) abroad, especially in the Middle East Region, is between the devil and the deep sea. Apart from reducing the government's responsibility to improve the economy by providing job opportunities, their presence also adds to the country's foreign exchange. However, on the other hand, the presence of TKI also adds to the problems caused by the lack of adequate legal protection, inadequate security and welfare guarantees, as well as the ups and downs of Indonesia's bilateral relations with the countries where they work as a result of the problems caused by the TKI themselves. Several policies related to sending migrant workers to the Middle East have been adopted since the time of President Susilo Bambang Yudhoyono. However, a firm policy was only taken during the administration of President Joko Widodo with the issuance of Minister of Manpower Decree number 260 of 2015 which stopped and prohibited the placement of Indonesian workers with individual users in Middle Eastern countries. This policy can also be seen as a policy that is outside the norm considering that the Middle East is the most popular region for migrant workers. This research attempts to explain how the ups and downs of the TKI issue are seen from a security perspective using a constructivist approach. This process, which the Copenhagen School calls securitization, attempts to place threats and objects that must be secured as products of the process of social interaction. This research will also look at how securitization occurs which is then followed by desecuritization and in its development becomes resecuritization.